Reduced Radiation Exposure Protocol during Computer Tomography of the Left Atrium Prior to Catheter Ablation in Patients with Atrial Fibrillation - Jadczyk, Tomasz; Wolf, Jiri; Pesl, Martin; Soucek, Filip; Lehar, Frantisek; Jez, Jiri; Kulik, Tomas; Tyshchenko, Bohdan; Belaskova, Silvie; Ourednicek, Petr; Caluori, Guido; Novak, Miroslav; et al. (Diagnostics (Basel, Switzerland), 2022)
(1) Background: Computer tomography (CT) is an imaging modality used in the pre-planning of radiofrequency catheter ablation (RFA) procedure in patients with cardiac arrhythmias. However, it is associated with a considerable ionizing radiation dose for patients. This study aims to develop and validate low-dose CT scanning protocols of the left atrium (LA) for RFA guidance. (2) Methods: 68 patients scheduled for RFA of atrial fibrillation were sequentially assigned to four groups of ECG-gated scanning protocols, based on the set tube current (TC): Group A (n = 20, TC = 33 mAs), Group B (n = 18, TC = 67 mAs), Group C (n = 10, TC = 135 mAs), and control Group D (n = 20, TC = 600 mAs). We used a 256-row multidetector CT with body weight-dependent tube voltage of 80 kVp (<70 kg), 100 kVp (70−90 kg), and 120 kVp (>90 kg). We evaluated scanning parameters including radiation dose, total scanning procedure time and signal-to-noise ratio (SNR). (3) Results: The average effective radiation dose (ED) was lower in Group A in comparison to Group B, C and D (0.83 (0.76−1.10), 1.55 (1.36−1.67), 2.91 (2.32−2.96) and 9.35 (8.00−10.04) mSv, p < 0.05). The total amount of contrast media was not significantly different between groups. The mean SNR was 6.5 (5.8−7.3), 7.1 (5.7−8.2), 10.8 (10.1−11.3), and 12.2 (9.9−15.7) for Group A, B, C and D, respectively. The comparisons of SNR in group A vs. B and C vs. D were without significant differences. (4) Conclusions: Optimized pre-ablation CT scanning protocols of the LA can reduce an average ED by 88.7%. Three dimensional (3D) models created with the lowest radiation protocol are useful for the integration of electro-anatomic-guided RFA procedures.
Keywords: catheter ablation; radiation; computed tomography